A Comparison Between a Resuscitation Glove and Standard Manual Compressions on the Quality of Cardiovascular Resuscitation - Kahsay, Desale Tewelde; Tommila, Miretta; Peltonen, Laura-Maria; Löyttyniemi, Eliisa; Xiao, Yu; Mauranen, Henry; Salanterä, Sanna (Ovid Technologies (Wolters Kluwer Health), 2026)
Background
Several audiovisual feedback (AVF) devices have been developed to monitor chest compression quality during cardiopulmonary resuscitation (CPR). However, most marketed stand-alone AVF devices are inflexible and rigid, causing discomfort and sometimes pain to the rescuers' hands.
Objective
The objective of this study was to evaluate the effectiveness and usability of a newly developed soft and flexible resuscitation glove designed to improve the quality of chest compressions during CPR.
Methods
We conducted a manikin-based randomized crossover study to compare the effectiveness of a newly developed AVF device (ResuGlove CPR Group) and standard CPR (Standard CPR Group) in improving the quality of chest compressions in simulated cardiac arrest cases. The usability of the newly developed ResuGlove was assessed using a System Usability Scale questionnaire.
Results
There were no significant differences in compression depth (mean, 53.69 vs 53.28; P = .70) and compression rate (mean, 111.48 vs 113.38; P = .23) between the ResuGlove CPR and Standard CPR groups. However, the group using ResuGlove had a higher percentage of complete chest releases between compressions (P = .008). Furthermore, the ResuGlove CPR Group had a significantly higher percentage of participants who performed chest compressions with adequate compression depth (82.8% vs 41.4%, P = .001) and compression rate (96.6% vs 72.4%, P = .012) compared with the Standard CPR Group. The ResuGlove usability score was calculated to be 70.4.
Conclusions
The newly developed ResuGlove significantly improved the quality of certain chest compression parameters, and the device's usability score was within the acceptable range.